Unit Tax versus Ad Valorem Tax: A Tax Competition Model with Cross-border Shopping - Hikaru Ogawa; Hiroshi Aiura (European Regional Science Association (ERSA), 2012)
Within the framework of spatial tax competition with cross-border shopping, we examine the choice of tax method between ad valorem tax and unit (specific) tax. The paper shows that governments endogenously choose ad valorem tax not because of a classic welfare reason, but because it is a good strategy in competing for mobile customers. Another key finding is that while governments are committed to the ad valorem tax method, the choice is not efficient; Tax-cutting competition becomes more serious when countries adopt ad valorem tax, and competition in ad valorem tax yields smaller payoffs than competition in unit tax.
Keywords: 330